Penggunaan Model PJBL Pada Pembelajaran Menulis Puisi Dengan Pemanfaatan Media Youtube Pada Peserta Didik Kelas X IPS-1 Semester II SMA Negeri 5 Palangka Raya Tahun Pembelajaran 2022/2023 - Klinton Sahputra Sitorus; Albertus Purwaka; Patrisia Cuesdeyeni; Petrus Poerwadi; Yulina Mingvianita (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to determine: (1) the use of the PjBL model in learning to write poetry by utilizing YouTube media for students, (2) the effect of using the PjBL model in learning to write poetry by using YouTube media for students. The approach used in this study is a quantitative approach in the form of writing poetry and qualitative with descriptive methods. The variables in this study are the use of YouTube media and the learning outcomes of students in learning to write poetry. The population in this study were all students of class X IPS SMA Negeri 5 Palangka Raya. The sample in this study were students of class X IPS-1 SMA Negeri 5 Palangka Raya who were obtained by purposive sampling technique. Data collection techniques used observation sheets of teacher and student activities as well as tests on writing poetry.